In Vitro Antidiabetic Activity Of Apis dorsata Binghami Nest Extract - Pratasik, Veronika; Mege, Revolson; Yermia, Mokosuli Semuel (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Indonesia is ranked 7th out of 10 countries with the highest number of people with diabetes mellitus, which is estimated to increase every year.Î± -amylase is an enzyme that catalyzes the hydrolysis of Î±-1,4 glycosidic bonds of polysaccharides to produce dextrins, oligosaccharides, maltose and D-glucose. Apis dorsata Binghami honeycomb contains secondary metabolites that have antidiabetic potential, including inhibiting the action of the Î±-amylase enzyme. The purpose of this study was to determine the in vitro antidiabetic potential of Apis dorsata binghami nest extract. This study uses a descriptive research method where the research data are obtained through laboratory experiments. Honeycomb extraction using maceration method. Analysis of total flavonoid content using UV-Vis spectrophotometric method. Antidiabetic potency test using -amylase enzyme inhibition method. The results of the extraction study showed that the % yield of the extract was 11.82% with a brownish yellow color. Analysis of the total flavonoid content showed the results of 3.33 mgQE/g. The inhibitory activity of the -amylase enzyme, the IC50 value of the extract obtained was 158.48Â±7.42 g/mL, the acarbose value was 165.96Â±7.08 g/mL. These results indicate that the extract of A.dorsata Binghami nest has hyperglycemic activity by inhibiting complex carbohydrate hydrolyzing enzymes such as inhibition of the -amylase enzyme which is better than acarbose because the IC50 value of the extract is smaller. If the IC50 value is smaller then the enzyme inhibition is stronger. For further research, it is recommended to use a more specific enzyme, namely the -glucosidase enzyme.